Status Keuangan Pada Perguruan Tinggi Negeri Badan Hukum - Firdaus, Firman; Fuad, Fokky; Rifai, Anis (Jurnal Bedah Hukum, 2025)
Abstract Legal Entity State Universities (PTN-BH) have initial wealth in the form of state wealth which is separated except for land, managed autonomously, both academic and non-academic. The problems that occurred in this study were regarding the financial status of PTN-BH, especially in financial management, which had implications for the audit criteria and financial accountability of PTN-BH. The autonomy of PTN-BH management is overlapping and ambiguous so that it always reaps controversy in its implementation. The formulation of the problem in this study discusses about; Is financial management at PTN-BH included in state financial management? and to what extent is the granting of autonomy to PTN-BH Universities in financial management? This research uses the theoretical framework of legal and financial certainty of the state. This research method is normative juridical using primary data on laws and regulations. The conclusion of this study shows that the financial management of PTN-BH is not part of the direct management of state finances but PTN-BH is given the right to independently manage all the initial and acquired wealth without eliminating legal responsibility to the state. Abstrak Perguruan Tinggi Negeri Badan Hukum (PTN-BH) memiliki kekayaan awal berupa kekayaan negara yang dipisahkan kecuali tanah, dikelola secara otonomi, baik akademik maupun non akademik. Permasalahan yang terjadi dalam penelitian ini yaitu mengenai status keuangan yang ada pada PTN-BH terutama dalam pengelolaan keuangan yang memiliki implikasi terhadap kriteria audit dan pertanggung jawaban keuangan PTN-BH. Otonomi pengelolaan PTN-BH mengalami tumpang tindih dan ambigu sehingga selalu menuai kontroversi dalam pelaksanaannya. Rumusan masalah dalam penelitian ini membahas mengenai; apakah pengelolaan keuangan pada PTN-BH termasuk kedalam pengelolaan keuangan negara? dan sejauh mana pemberian kewenangan otonomi pada Perguruan Tinggi PTN-BH dalam pengelolaan keuangan? Penelitian ini menggunakan kerangka teori kepastian hukum dan keuangan negara. Metode penelitian ini yaitu yuridis normatif dengan menggunakan data primer peraturan perundang-undangan. Kesimpulan penelitian ini menunjukkan bahwa pengelolaan keuangan PTN-BH bukanlah termasuk bagian dari pengelolaan keuangan negara secara langsung namun PTN-BH diberikan hak mengelola secara mandiri seluruh kekayaan awal maupun yang diperolehnya tanpa menghilangkan pertanggung jawaban hukum kepada negara.